2004
DOI: 10.1249/01.mss.0000125157.49280.af
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Commercial Herbal-Based Formula on Exercise Performance in Cyclists

Abstract: A 2-wk ingestion schema of a commercial herbal-based formula is insufficient to elicit positive changes in cycling performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 24 publications
3
39
1
1
Order By: Relevance
“…These findings support those of Colson et al [16] and Earnest et al [17] who tested the effect of an herbal blend primarily composed of Cordyceps sinensis and R rosea on cycling exercise and found that it failed to impact performance or any associated physiologic variable, including heart rate, VȮ 2 , and lactate and ventilation thresholds. However, our results are at odds with the conclusions of other investigators [3,7,8] who reported observing an ergogenic effect of R rosea ingestion.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings support those of Colson et al [16] and Earnest et al [17] who tested the effect of an herbal blend primarily composed of Cordyceps sinensis and R rosea on cycling exercise and found that it failed to impact performance or any associated physiologic variable, including heart rate, VȮ 2 , and lactate and ventilation thresholds. However, our results are at odds with the conclusions of other investigators [3,7,8] who reported observing an ergogenic effect of R rosea ingestion.…”
Section: Discussionsupporting
confidence: 88%
“…We were not comfortable giving such a large dose because of unlikely but potential central nervous system stimulation actions. However, our dosage far exceeded the manufacturer's recommended amount and was 100% to 400% greater than that used in most other human studies [3,8,16,17]. Only Wing et al [6] administered a higher dosage (1778 mg/d) to human subjects.…”
Section: Discussionmentioning
confidence: 68%
“…Compared with the placebo group, acute intake of R. rosea extract increased the time to exhaustion slightly but significantly; however, daily intake of the drug for 4 weeks produced no significant difference compared with placebo treatment. These results contrast with several other studies where significant effects on mental and physical performance following repeated administration of R. rosea extract have been observed (Darbinyan et al, 2000;Spasov et al, 2000a, b) Very recently, a study involving a commercial, herbal-based formula containing root of R. rosea appeared to demonstrate that the preparation did not elicit positive changes in cycling performance (Earnest et al, 2004). The discrepancy of the results from this study compared with the numerous other studies require explanation.…”
contrasting
confidence: 99%
“…This observed effect may be due to the presence of carbohydrates (45-51% of dry weight) and polysaccharides (210KD 9 ) in the Indian isolate of Cordyceps sinensis , which has been earlier reported to promote endurance and energy metabolism (Manabe et al, 2000;Li and Li, 2009). In contrary, a number of human studies using trained cyclists have also reported the inefficiency of CS and CS-based commercial supplements (Earnest et al, 2004;Parcell et al, 2004;Colson et al, 2005;Herda et al, 2008) in improving performance. However, these studies have been conducted with athletes who have attained their maximum metabolic and ventilatory response and the scope of endurance improvement is minimal.…”
Section: Discussionmentioning
confidence: 97%
“…The proposed reasons for the observed increased energy output by CS supplementation are stabilization of blood sugar metabolism and increased ATP production. But an equivocal number of studies have also reported ineffectiveness of CS and CS-based energy supplements in increasing the exercise capacity in competitive cyclists (Parcell et al, 2004;Earnest et al, 2004;Colson et al, 2005). Irrespective of these reports, molecular studies assessing the effectiveness of CS supplementation on skeletal muscle metabolic programme and resulting effects on exercise endurance is lacking.…”
Section: Introductionmentioning
confidence: 99%